Point-of-care biosensor for stroke biomarker detection - Ng, Timothy Si En (2017)
There is demand for Point-of-care devices for stroke sub-type diagnostic application. Current lateral flow assays demonstrated high specificity but low sensitivity. The Stackpad biosensor is a modification to the lateral flow assays in order to achieve a more sensitive Point-of-care device. The proof of concept was done earlier for detection of bacteria. This report optimized the factors affecting the Stackpad biosensor, allowing for further developmental testing of the device with actual samples and target stroke biomarkers. It worked on improving the flow by observing ink and water flow in the device. Membrane modification procedures and the colorimetric signal were studied by comparing with both the ELISA and Stackpad testing. After optimization, the flow of the novel device was improved with the separation layer and addition of Tween20. The Stackpad biosensor also takes less than 5 minutes to achieve response. The procedure for immobilizing HRP-conjugated antibodies on the Conjugate and release pads was also optimized to achieve acceptable level of signals. TMB was also determined to be a suitable colorimetric substrate in a 1-step Point-of-care device.